Complete switch from α-2, 3- to α-2, 6-regioselectivity in Pasteurella dagmatis β-d-galactoside sialyltransferase by active-site redesign. Issue 15 (26th January 2015) - Schmölzer, Katharina; Czabany, Tibor; Luley-Goedl, Christiane; Pavkov-Keller, Tea; Ribitsch, Doris; Schwab, Helmut; Gruber, Karl; Weber, Hansjörg; Nidetzky, Bernd
Abstract : Incorporation of Pro7His and Met117Ala substitutions resulted in a completely regioselective and highly efficient α-2, 6-sialyltransferase. Abstract : Structure-guided active-site redesign of a family GT-80 β-d -galactoside sialyltransferase (from Pasteurella dagmatis ) to change enzyme regioselectivity from α-2, 3 in the wild type to α-2, 6 in a P7H–M117A double mutant is reported. Biochemical data for sialylation of lactose together with protein crystal structures demonstrate highly precise enzyme engineering.